PEMODELAN DAN PERANCANGAN GAS COOLER UNTUK MESIN REFRIGERASI CO2 - Willy Adriansyah (Mesin, 2003)
Gas cooler is one of the important components in CO2 refrigeration system and it must be designed properly. Conventional mathematical modeling used in designing heat exchanger have some drawbacks when the working fluid has large variation on its thermo physical properties. This paper discusses detail modeling and designing one of heat exchanger types which takes into account unique characteristic of CO2 as refrigerant. The mathematical model is then validated by experimental data. The comparison shows that the model predicts gas cooler performance within 2% maximum deviation. The principles of modeling can be applied to various types of heat exchanger.